2022
DOI: 10.1126/sciimmunol.abn5311
|View full text |Cite
|
Sign up to set email alerts
|

Recall of B cell memory depends on relative locations of prime and boost immunization

Abstract: Immunization or microbial infection can establish long-term B cell memory not only systemically but also locally. Evidence has suggested that local B cell memory contributes to early local plasmacytic responses after secondary challenge. However, it is unclear whether locality of immunization plays any role in memory B cell participation in recall germinal centers (GCs), which is essential for updating their B cell antigen receptors (BCRs). Using single B cell culture and fate mapping, we have characterized BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
27
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 62 publications
8
27
3
Order By: Relevance
“…A still lower contribution of MBCs to recall GCs was reported in the setting of a boost in the contra-lateral footpad, but values similar to ours were mentioned in this study for an intraperitoneal immunization ( 20 ). This is in line with a recent paper which shows the preferential participation of MBCs to recall GCs in local boost condition ( 32 ). In the case of an SRBCs challenge that generates robust secondary GCs comprising several millions of cells, the contribution of MBCs, even minor, still represents a considerable cell fraction that will undergo new rounds of maturation.…”
Section: Discussionsupporting
confidence: 93%
“…A still lower contribution of MBCs to recall GCs was reported in the setting of a boost in the contra-lateral footpad, but values similar to ours were mentioned in this study for an intraperitoneal immunization ( 20 ). This is in line with a recent paper which shows the preferential participation of MBCs to recall GCs in local boost condition ( 32 ). In the case of an SRBCs challenge that generates robust secondary GCs comprising several millions of cells, the contribution of MBCs, even minor, still represents a considerable cell fraction that will undergo new rounds of maturation.…”
Section: Discussionsupporting
confidence: 93%
“…A second is that with the detection of shared clones with high mutational load in lymph nodes at different sites and in the blood, the data of Lee et al 2 are consistent with MBCs re-entering ongoing GCs for further affinity maturation and selection. In contrast to the potentially insignificant participation of MBCs reported during secondary GC responses 11 , re-recruitment here, in particular within the same anatomical site 12 , may commonly occur. That is, the observed rarity of MBCs with low mutational load could either be due to their gradual consumption through repeated re-entry or reflect a ‘dilution’ through continued MBC output.…”
contrasting
confidence: 63%
“…Serum antibody titers were higher after ipsilateral versus contralateral boosting. A recent report indicated that affinity maturation was also enhanced by same-site boosting, suggesting that ipsilateral boosting may offer advantages for humoral immunity ( 61 ). Opposite-site boosting readily affected T cell responses.…”
Section: Discussionmentioning
confidence: 99%